The effect of stellate ganglion block on postoperative recovery quality in peri-menopausal women undergoing gynecological laparoscopic surgery - Yuan, Xueling; Tang, Yijie; Xie, Xiyuan; Qiu, Jiapeng; Han, Yupeng; Ke, Peng; Zheng, Chengjie; Zeng, Kai; Wu, Xiaodan (Frontiers in Medicine, 2025)
ObjectiveThis study aims to observe whether right-sided stellate ganglion block (SGB) before surgery can improve early postoperative recovery quality in peri-menopausal women undergoing elective gynecological laparoscopic surgery.MethodsNinety-four peri-menopausal women, who meet the inclusion criteria, scheduled for gynecological laparoscopic surgery were selected (Trial Registration: ChiCTR2200057907, March 21, 2022). They were randomly assigned into two groups (Group S and Group C). Group S received right-sided SGB under ultrasound guidance, combined with tracheal intubation and general anesthesia, with an injection of 4 mL of 0.2% ropivacaine. Group C underwent only ultrasound scanning combined with tracheal intubation and general anesthesia. The primary outcome was postoperative recovery quality at 24 h, assessed using the 40-item Quality of Recovery (QoR-40) questionnaire. Secondary outcomes included: (1) Heart rate (HR) and Mean Arterial Pressure (MAP); (2) Resting pain scores; (3) Recovery of gastrointestinal function postoperatively; (4) Postoperative adverse reactions within 24 h.ResultsAt 24 h postoperative, Group S had a higher QoR-40 total score compared to Group C with a corrected mean difference of 12.50. Significant differences in HR were noted at T3, T5, and T6, and in MAP at T2, T4, T6, and T7. The resting pain scores at 4, 8, and 12 h postoperatively differed significantly between the two groups. (4) Compared with Group C, Group S had a shorter time to first flatus and a shorter time to the first return of bowel sounds. The incidence of postoperative abdominal distension was lower in Group S compared to the Group C. (5) The incidence of postoperative nausea, vomiting, headache, shoulder pain, and throat pain was lower in Group S than Group C, with statistically significant differences.ConclusionPreoperative single-session stellate ganglion block improves 24-h postoperative recovery in peri-menopausal women undergoing gynecological laparoscopic surgery by alleviating pain, stabilizing hemodynamics, promoting gastrointestinal recovery, and reducing postoperative adverse reactions.Clinical trial registrationwww.chictr.org.cn, identifier ChiCTR2200057907.